analisis kebutuhan modal kerja pada cv yola intan mandiri di bontang - Irma Yuliana; Iskandar Iskandar; Dhina Mustika Sari (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2018)
The research method used in this study is the working capital turnover method. Working capital requirements is determined by comparing income in 2017 (using CV Yola Intan Mandiri’s income estimate) with working capital turnover in 2016. Results of the study show that in 2017 the working capital that is required is 294.206.150 rupiah while the available working capital is 262.868.304 rupiah. These data indicate that CV Yola Intan Mandiri’s working capital has deficiency amounting to 31.337.846 rupiah. Therefore, the available working capital is not enough to cover the working capital requirements in order to support fluency of CV Yola Intan Mandiri operational activities in 2017. Keywords: Working Capital, Working Capital Need, Working Capital Turnover Method